IMPORTANCE OF RAKTAMOKSHANA IN THE MANAGEMENT OF TVACHAVIKAR - *Tekade Anand; Daulatkar Kavita (International Journal of Ayurveda and Pharma Research, 2018)
Nowadays Tvachavikar is most common skin disease, and it has social impact. It is a skin problem mentioned in Ayurvedic literature with Kapha and Pitta morbidly or pathology. In classical different text of Ayurveda and Acharyas emphasize the Shodhana therapy as the line of treatment at various places. In Shodhana treatment Raktamokshan is highlight specially because in Samprapti Ghataka Rakta is mainly involved as Dushya. In the present topic, Raktamokshana Acharya Sushruta propounds practical guidelines for bloodletting and claims it as most effective therapy in half of the body ailments. In all different methods for bloodletting such as Jalaukavacharana Karma, Prachhanna Karma and Siravedhana Karma, Jalaukaavacharna Karma (leech therapy) is considered as the ideal method to expel out the vitiated blood safely, quickly, and effectively. The vitiated external environment undoubtedly affects the body’s internal ailments. Large community prevalence studies have demonstrated that about 20-30% of the world population have various skin problems requiring attention. So Raktamokshan is one of the important Panckarma treatments to cure various type of Tvacha vikar highlighting in this topic.